2017
DOI: 10.1177/0022034517733958
|View full text |Cite
|
Sign up to set email alerts
|

Retention Improvement in Fluoride Application with Cold Atmospheric Plasma

Abstract: This study aimed to apply fluoride formulations to enamel with cold atmospheric plasma (CAP) and analyze the fluoride uptake, retention, and acid resistance quantitatively. Human enamel specimens were divided randomly into 2 groups: group APF1, 1.23% acidulated phosphate fluoride (APF) gel; group APF2, 1.23% APF gel with CAP. Fluoride and CAP were applied to the samples 4 times at 1-wk intervals. The specimens were also stored in artificial saliva for 4 wk to evaluate the retention of fluoride. The fluoride co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
1
17
1
Order By: Relevance
“…CAP eliminates remaining pathogens and alters the tooth surface. CAP treatment showed an increase in bonding strength in the dentin–adhesive interface [ 79 , 80 , 81 ] and enhanced enamel remineralization [ 82 , 83 ]. This may prevent secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…CAP eliminates remaining pathogens and alters the tooth surface. CAP treatment showed an increase in bonding strength in the dentin–adhesive interface [ 79 , 80 , 81 ] and enhanced enamel remineralization [ 82 , 83 ]. This may prevent secondary caries.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the erosive challenge, the specimens in the CAP groups underwent treatment with a plasma jet (Medaion, Nik Fanavaran Plasma Co., Tehran, Iran) using helium gas at a flow rate of 2 L/min with a potential difference of 4 kV, and 20 kHz frequency such that the nozzle tip had a maximum distance of 10 mm from the tooth surface [ 21 ] ( Figure 1 ). Next, the specimens were subjected to different fluoride varnishes according to their experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, cold atmospheric plasma (CAP) has been used for root canal sterilization, enhancement of bond strength, and tooth bleaching [ 18 20 ]. Kim et al [ 21 ] showed that helium CAP prior to varnish application enhanced the uptake of fluoride ions by the enamel surface. Moreover, evidence shows that the effects of CAP treatment in combination with fluoride last for a longer period of time compared with the effects of fluoride alone.…”
Section: Introductionmentioning
confidence: 99%
“…So uoride application can produce a large amount of calcium uoride and uorapatite when hydroxyapatite of tooth is treated with plasma. In our previous study, as for the resistance to demineralization, the calcium-to-phosphate ratio of the enamel treated with APF and nonthermal atmospheric plasma was higher than that treated with APF alone, and it increased with the frequency of treatment [30]. So the combination treatment of nonthermal atmospheric plasma and uoride improves retention of uoride on the enamel and resistance to demineralization when compared with treatment with uoride alone.…”
Section: Discussionmentioning
confidence: 81%